Correlación experiencia: Teoría en el reactor RA-3 - Pasquini, E.; Solanilla, R.B.A.; Ricabarra, G.H.; Rapoport, H.; Pieroni, N.B. (Comisión Nacional de Energía Atómica (CNEA), 1971)
Fil:Pasquini, E. Comisión Nacional de Energía Atómica (CNEA). República Argentina